(untitled) (Revista Brasileira Multidisciplinar, 2023)
In the tireless pursuit to make an education more interesting and stimulating, which leads students to appropriate knowledge in an engaged and well-founded way, having applications in their daily lives, it is that researchers in the field of Science Teaching seek to innovate. After the Second World War, a period of scientific and technological development that was not concerned with environmental and social issues, a movement called Science, Technology and Society (STS) emerged, aiming to promote the interest of students, wtih discuss social and ethical implications, understanding the nature of science and scientific work. The desire to form critical people with scientific and technological thinking brought the STS approach to the educational field. Therefore, this study aimed to investigate the perception of high schoolers from a public school in the municipality of Pontal do Paraná, state of Paraná, in the face of the environmental disaster that occurred in the city of Brumadinho in January 2019, based on a STS proposal, involving scientific questions from the point of view of chemistry linked to tailings dams, listing subjects related to the subject, such as “Concentration of Solutions” and showing the importance of chemistry in environmental issues. The results obtained in the application served to affirm that diversifying the teaching methodologies can be promising and very interesting in the formation of citizenship.